Case report: Personalized triple phage-antibiotic combination therapy to rescue necrotizing fasciitis caused by Panton-Valentine leukocidin-producing MRSA in a 12-year-old boy - Van Nieuwenhuyse, Brieuc; Balcaen, Mathilde; Chatzis, Olga; Haenecour, Astrid; Derycke, Emilien; Detaille, Thierry; Clément de Cléty, Stéphan; Boulanger, Cécile; Belkhir, Leïla; Yombi, Jean-Cyr; De Greef, Julien; Cornu, Olivier; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Maximal standard-of-care (SOC) management could not stop the life-threatening progression of a necrotizing fasciitis induced by Panton-Valentine Leukocidin-producing Methicillin-Resistant Staphylococcus aureus (MRSA) in a 12-year-old boy. Multi-route phage therapy was initiated along with antibiotics against Staphylococcus aureus, Pseudomonas aeruginosa and Stenotrophomonas maltophilia, eventually leading to full recovery with no reported adverse events.